2016
DOI: 10.18203/2349-2902.isj20161159
|View full text |Cite
|
Sign up to set email alerts
|

Limberg flap reconstruction following rhomboid excision of the sacrococcygeal pilonidal sinus

Abstract: Background: Pilonidal sinus disease has been treated with various techniques. There is still no consensus about treatment. However, a long list of surgical techniques available reflects the inability to find an ideal procedure for the treatment. The rhomboid flap of limberg is a transposition flap that has been advocated for treatment of this condition. The objective of this study was to evaluate the limberg flap reconstruction for pilonidal sinus in terms of complications, hospitalization time, days to return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…An additional procedure of secondary suture was required only in one patient (about 3%). 5 In another large series comprising 411 patients with pilonidal sinus who underwent Rhomboid excision and Limberg flap, complications like seroma and wound infection each occurred in about 3%. 6 In both series, the drain was placed in all cases routinely.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…An additional procedure of secondary suture was required only in one patient (about 3%). 5 In another large series comprising 411 patients with pilonidal sinus who underwent Rhomboid excision and Limberg flap, complications like seroma and wound infection each occurred in about 3%. 6 In both series, the drain was placed in all cases routinely.…”
Section: Resultsmentioning
confidence: 98%
“…Most of the series showing successful use of this method in treating pilonidal disease has used drain. 2,4,5 However, one of the studies showed no difference in recurrence when the drain was placed. 8 There seems to be no consensus about when to remove the drain and no studies done regarding the duration drain should be kept to reduce the infection.…”
Section: Discussionmentioning
confidence: 99%